The Muscidae described by J. W. Zetterstedt (Insecta: Diptera) - Pont, Adrian C.; Bergström, Christer; Pont, Adrian C. (Zootaxa, 2011)
The 204 species-group names of Muscidae proposed by J.W. Zetterstedt, including the species described by Stenhammar and Wahlberg in Zetterstedt, are reviewed. Excluded from this total are the nomina nuda listed in Zetterstedt (1837, 1845). Of these 204 names, 192 are available names, whilst 10 are unavailable because they are nomina nuda or were proposed in synonymy and not made available before 1961 (Aricia atrata, Anthomyza bicolor, Cyrtoneura coerulescens, Cyrtoneura curvinervis, Anthomyza insignita, Pyrellia luteipennis, Pyrellia parviceps, Aricia pulchella, Anthomyza pusilla, Aricia sororia), and two are unjustified emendations (Anthomyza ocreata, Anthomyza trigonota). Of the 192 available names, 85 are valid species whilst 107 are now placed in synonymy. In this review, 106 lectotypes are designated. Three names are raised from synonymy and are given new status as valid species: Mydaea detrita (Zetterstedt, 1845), Lophosceles impar (Zetterstedt, 1846), and Helina lapponica (Ringdahl, 1918). Fourteen new synonyms are proposed: Anthomyza cingulipes Zetterstedt, 1849 with Anthomyza (now Coenosia) bilineella Zetterstedt, 1838, Anthomyza nigrifemur Zetterstedt, 1845 with Palusia (now Coenosia) testacea Robineau-Desvoidy, 1830, Anthomyza cineraria Zetterstedt, 1845 with Anthomyza (now Helina) fratercula Zetterstedt, 1845, Anthomya veterana Zetterstedt, 1838 with Anthomyza (now Helina) longicornis (Zetterstedt, 1838), Anthomyza nivalis Zetterstedt, 1838 with Aricia (now Helina) flavisquama Zetterstedt, 1849, Aricia duplaris Zetterstedt, 1845 with Anthomyia (now Helina) obscurata Meigen, 1826, Lonchaea metallica Zetterstedt, 1849 with Anthomyia (now Hydrotaea) capensis Wiedemann, 1818, Anthomyza hians Zetterstedt, 1846 with Musca (now Lophosceles) mutatus Fallén, 1823, Anthomyza electa Zetterstedt, 1860 with Anthomyza (now Mydaea) detrita Zetterstedt, 1845, Anthomyza humeralis Zetterstedt, 1845 and Anthomyza humeralis Zetterstedt, 1860 with Mydaea setifemur Ringdahl, 1924, Anthomyza vicina Zetterstedt, 1838 with Anthomyza (now Phaonia) consobrina Zetterstedt, 1838, Aricia fumipennis Zetterstedt, 1845 with Anthomyza (now Spilogona) arctica Zetterstedt, 1838, and Anthomyza hirsutula Zetterstedt, 1838 with Anthomyza (now Thricops) innocua Zetterstedt, 1838. Following Reversal of Precedence, Helina flavisquama is preserved as a nomen protectum and Helina nivalis rejected as a nomen oblitum.